Experimental quantum simulation of fermion-antifermion scattering via boson exchange in a trapped ion - Xiang Zhang (Nature Portfolio, 2018)
Simulation of quantum field theory using quantum systems would in principle allow avoidance of the exponential overhead required for classical simulations. Here, the authors use a multilevel trapped ion to simulate the processes of self-interaction and particle-antiparticle creation/annihilation.